Currency Returns, Intrinsic Value, and Institutional‐Investor Flows - FROOT, KENNETH A.; RAMADORAI, TARUN (Journal of Finance, 2005)
ABSTRACT We decompose currency returns into (permanent) intrinsic‐value shocks and (transitory) expected‐return shocks. We explore interactions between these shocks, currency returns, and institutional‐investor currency flows. Intrinsic‐value shocks are: dwarfed by expected‐return shocks (yet currency returns overreact to them); unrelated to flows (although expected‐return shocks correlate with flows); and related positively to forecasted cumulated‐interest differentials. These results suggest flows are related to short‐term currency returns, while fundamentals better explain long‐term returns and values. They also rationalize the long‐observed poor performance of exchange‐rate models: by ignoring the distinction between permanent and transitory exchange‐rate changes, prior tests obscure the connection between currencies and fundamentals.